Monitoring with Lichens - Monitoring Lichens - Nimis, Pier Luigi; Scheidegger, Christoph; Wolseley, Patricia A. (Springer Netherlands, 2002)
A comprehensive, up-to-date review of lichens as biomonitors of air pollution (bioindication, metal and radionuclide accumulation, biomarkers), and as monitors of environmental change (including global climate change and biodiversity loss) in a wide array of terrestrial habitats. Several methods for using lichens as biomonitors are described in a special section of the book
Keywords: Environment; Pollution, general; Plant Sciences; Ecology; Atmospheric Protection/Air Quality Control/Air Pollution; Nature Conservation; Plant Ecology; Plant ecology; Plant science; Botany; Nature conservation; Pollution; Air pollution; Biomonitoring; Flechten; Konferenzschrift; Aufsatzsammlung